Hematologic and Non-Hematologic Side Effects in Lung Cancer Patients Post Chemotherapy at Arifin Achmad General Hospital - Oinike, Irene; Munir, Sri Melati (Respiratory Science, 2025)
Background: Lung cancer is the second-highest cause of malignancy in the world, with a prevalence of 11.4% of all types of cancer. The majority of lung cancer patients are diagnosed at an advanced stage; therefore, chemotherapy acts as palliative therapy without curative therapy options. Chemotherapy drugs have various side effects, both hematologic and non-hematologic. Thus, monitoring side effects should be notable to improve the quality of life for patients with lung cancer undergoing chemotherapy. Method: This research was a descriptive study with a total sampling data collection technique. Samples were collected for 6 months according to the inclusion criteria, and the results were presented in the form of a distribution table. Results: During August 2023 to January 2024, 29 lung cancer patients met the inclusion criteria at Arifin Achmad General Hospital. Of these 29 patients, 25 (86.21%) were men and 4 (13.79%) were women. The hematologic side effects were observed in 16 (55.17%) patients, while non-hematologic side effects were found in 18 (62.07%) patients. The most common hematologic side effect is anemia, and the most common non-hematologic side effect is gastrointestinal disorders. Conclusion: The chemotherapy regimen used for lung cancer patients caused both hematologic and non-hematologic side effects. The non-hematologic side effects were more common than the hematologic.